Profitability and productivity of drought tolerant rice variety Binadhan-21 in some selected areas of Bangladesh - Sultana, R; Rahman, MH; Haque, MR; Sarkar, MMA; Islam, S (Bangladesh Journal of Nuclear Agriculture, 2023)
The study was conducted in five major BINA developed Aus rice growing areas of Bangladesh, namely Mymensingh, Rangpur, Kushtia, Chapai Nawabganj and Magura district. The study focused on the profitability and productivity of Binadhan-21; and the major constraints to Binadhan-21 production. Simple random sampling technique was followed for this study. A total of 100 farmers were randomly selected as sample size in the study areas, 20 from each district. Data were collected from Aus rice growers through interview schedule. Collected data were edited, summarized, tabulated and analyzed to fulfill the objectives. Some descriptive statistics were used. Binadhan-21 production is highly profitable in the study area. The average yield was 4.86 t ha-1 in Aus season and undiscounted BCR was 1.93. Therefore, Binadhan-21 farmers received high return on its investment. The farmers in the study areas encountered some constraints to Binadhan-21 production. The first ranked was unavailability of seeds in all areas. Other constraints were lack of training (70.83%), crop lost by bird and animal (56.61%), and natural calamities (19.30%). Bangladesh J. Nuclear Agric, 37(1): 111-116, 2023